Festiwal a miasto. Przykład Edynburga - Kowalska, Marta (Studia Etnologiczne i Antropologiczne, 2016)
The aim of this article is to show Edinburgh as a city identified by its festivals. Two of them—Edinburgh International Festival and Edinburgh Festival Fringe—influenced cultural landscape of Scottish capital the most, and therefore they were analyzed extensively in this study. I intend to show how the concepts of “space” and “place” surface in the reception of the Edinburgh festivals. I’m presenting both—the residents’ and visitors’—perspectives. I’m trying to better understand how the city, art, and people collide, cooperate and—in the end—coexist.